Pulmonary rehabilitation program of 36 sessions improves functional capacity and reduce body mass level in patients with chronic obstructive pulmonary disease - Paulo Sergio Correia Martins; Débora Ferreira Moraes Guimarães; Roger Medeiros Xavier; Alessandra de Magalhães Campos Garcia; Matheus Gomes Castro; Cristiano Teixeira Mostarda; Antonio Coppi Navarro (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2022)
Aim: To evaluate the functional capacity through the 6-minutes walk test and the body mass level in patients with Chronic Pulmonary Obstructive Disease, Pulmonary Rehabilitation Program participants, in pre moments, 18 sessions and in the end of 36 sessions. Materials and Methods: In the Pulmonary Rehabilitation Program with 3 weekly sessions per a period of 12 weeks of combine exercises (aerobic and strength), it was realized the 6-minutes walk test, to check the functional capacity, before, 18 sessions and after 36 sessions of Pulmonary Rehabilitation; 20 patients diagnosed with CPOD (15 with moderate CPOD and 5 with grave CPOD) were evaluated; it was also checked the Body Mass Index (BMI) from patients in the same time. Results: It was checked distance covered increase in the 6-minutes walk test, in 18 sessions and in the end of 36 sessions from the program; it was checked the patients' BMI decrease in the end of 36 sessions from rehabilitation program. Discussion: In 18 sessions, it was observed an improvement of 18.75%, as well as in 36 sessions the improvement was 29.47% of covered distance by patients in the 6-minutes walk test; after 18 sessions it has already happened a 3% decrease in BMI and also, with 36 sessions this decrease was 6.24%, showing that way the Pulmonary Rehabilitation Program's efficiency. Conclusion: After 36 sessions, the pulmonary rehabilitation is effective in the improvement of functional capacity and in BMI decrease on patients with COPD.